Strategies of business plans - Wang, Wei; Kobielieva, T. O.; Khodyrieva, O. O. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The report suggests methods for improving business planning that can serve as a starting point for strategy development. Every business has its own unique characteristics, so it's important to develop a plan that meets your business's specific needs and goals.
Стратегії бізнес-планів
Keywords: business plan; development strategy; characteristics; planning; efficiency; enterprises